Efektivitas Self Hypnosis Dan Musik Klasik Terhadap Emesis Gravidarum Pada Ibu Hamil Trimester I - Abrianthi, Ayu Kartika; Widiastini, Luh Putu; Karuniadi, I Gusti Agung Manik; Purnamayanthi, Pande Putu Indah (STIKes Budi Mulia Sriwijaya, 2025)
There are high cases of pregnant women experiencing discomfort in the first trimester such as nausea and vomiting. Researchers are looking for non-pharmacological solutions to this problem, namely self-hypnosis and classical music therapy. The aim of this research is to determine the effectiveness of self-hypnosis and classical music on emesis gravidarum in trimester pregnant women. The research method used was Quasi Experimental with Pretest Posttest Nonequivalent Control Group Design. The samples used in this study were pregnant women in the first trimester, 8 to 12 weeks of gestation who experienced nausea and vomiting with a frequency of <5 times, between 3-4 times in the morning and evening at Payangan General Hospital, a total of 44 respondents who were divided into two groups. control and treatment using accidental sampling technique. The treatment group was given a recording containing classical musical accompaniment accompanied by self-hypnosis which could be listened to on the respondent's cell phone using a headset. Done for 20 minutes twice a day in the morning and evening for 3 consecutive days. The results of this study showed a significant effect of providing self-hypnosis and classical music on the level of emesis gravidarum in first trimester pregnant women with a p value of 0.001 (p<0.05). It is hoped that the results of this research can provide education about the importance of providing self-hypnosis and classical music to pregnant women as an effort to improve services, especially in the management of emesis gravidarum